2019
DOI: 10.5334/jcr.175
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of Circadian Rhythm Gene Expression in Cystic Fibrosis Mice

Abstract: Cystic fibrosis (CF) is autosomal recessive disease that affects multiple body systems. CF patients often experience sleep disturbances, altered sleep patterns, and sleep apnea. Sleep in mammals is controlled in part by circadian clock genes, including Clock, Bmal1, Period1, Period2, Cryptochrome1, and Cryptochrome2 . The purpose of this study was to gain a better understanding of the biological underpinnings of disordered sleep experienced in CF. To accomplish thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…It has always been widely assumed that CF-related symptoms are the primary cause of sleep disruption in CF patients, as described above [24]. However, recent studies implicate circadian rhythm disturbances and CFTR dysfunction as potential causes of sleep disturbances in CF patients [34].…”
Section: The Cftr Gene and Circadian Rhythms Disturbancesmentioning
confidence: 98%
See 2 more Smart Citations
“…It has always been widely assumed that CF-related symptoms are the primary cause of sleep disruption in CF patients, as described above [24]. However, recent studies implicate circadian rhythm disturbances and CFTR dysfunction as potential causes of sleep disturbances in CF patients [34].…”
Section: The Cftr Gene and Circadian Rhythms Disturbancesmentioning
confidence: 98%
“…Barbato et al collected tissue samples from both CF-afflicted and healthy mice counterparts and compared tissue samples obtained from both groups in both standard and sleep-deprived states [34]. They found that the CF group had a significant expression of dysregulated circadian clock genes, which they assumed was due to loss of CFTR functionality [21].…”
Section: The Cftr Gene and Circadian Rhythms Disturbancesmentioning
confidence: 99%
See 1 more Smart Citation
“…That rhythmic expression is regulated by a self-contained feedback loop which is integral to the function of the CTS. Dysfunction of the system, caused by endogenous or exogenous factors, has been linked to many disease processes, including disordered sleep, anxiety and depression, cardiac disease, immune dysfunction, and many others [ 4 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many genes and their protein products have been associated with the CTS, some of which include Clock, Bmal1, Period1, Period2, Cryptochrome1 , and Cryptochrome2 [ 5 6 ]. The core molecular functionality of the CTS, including its unique process of self-regulating gene expression, has been well described [ 4 7 8 ].…”
Section: Introductionmentioning
confidence: 99%